Brief research report: in-depth immunophenotyping reveals stability of CD19 CAR T-cells over time - Odak, Ivan; Bayir, Lâle M.; Riemann, Lennart; Sikora, Ruth; Schneider, Jessica; Xiao, Yankai; Möhn, Nora; Skripuletz, Thomas; Beutel, Gernot; Eder, Matthias; Ganser, Arnold; Förster, Reinhold; et al. (Frontiers in Immunology, 2024)
Variability or stability might have an impact on treatment success and toxicity of CD19 CAR T-cells. We conducted a prospective observational study of 12 patients treated with Tisagenlecleucel for CD19 + B-cell malignancies. Using a 31-color spectral flow cytometry panel, we analyzed differentiation stages and exhaustion markers of CAR T-cell subsets prior to CAR T-cell infusion and longitudinally during 6 months of follow-up. The majority of activation markers on CAR T-cells showed stable expression patterns over time and were not associated with response to therapy or toxicity. Unsupervised cluster analysis revealed an immune signature of CAR T-cell products associated with the development of immune cellassociated neurotoxicity syndrome. Warranting validation in an independent patient cohort, in-depth phenotyping of CAR T-cell products as well as longitudinal monitoring post cell transfer might become a valuable tool to increase efficacy and safety of CAR T-cell therapy.